2000
DOI: 10.14712/18059694.2019.121
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Adhesion Molecules (sICAM-1, sVCAM-1 and sE-Selectin) in Healthy School Aged Children and Adults

Abstract: The aim of this study was to map normal levels of serum soluble isoforms of adhesion molecules in relation to age and sex in the group of school-aged children. sICAM-1, sVCAM-1 and sE-selectin were determined in the group of 158 normal children subdivided into two subgroups; 6-10 years (68 children, median age 8 years) and 11-15 years (90 children, median age 12 years) and in 70 normal adult blood donors (25 females and 45 males, median age 46 years). The levels of sICAM-1 and sE-selectin fell down significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Further, the study authors did replicate and validate their results in a group of outpatient subjects from a hepatology clinic, a population more closely reflecting the participants in our study. Typically serum VCAM-1 ranges are approximately 340–1150 ng/mL in healthy adults [32], and we observed ranges from 391–1669 ng/mL in NAFLD/NASH patients. However, there is an order of magnitude difference between our study values and the Lefere results, which may be related to the measurement process, stressing the need for assay validation.…”
Section: Discussionmentioning
confidence: 59%
“…Further, the study authors did replicate and validate their results in a group of outpatient subjects from a hepatology clinic, a population more closely reflecting the participants in our study. Typically serum VCAM-1 ranges are approximately 340–1150 ng/mL in healthy adults [32], and we observed ranges from 391–1669 ng/mL in NAFLD/NASH patients. However, there is an order of magnitude difference between our study values and the Lefere results, which may be related to the measurement process, stressing the need for assay validation.…”
Section: Discussionmentioning
confidence: 59%
“…TNF‐alpha stimulates the expression of adhesion molecules (E‐selectin, P‐selectin) and intercellular adhesion molecule 1 (ICAM‐1) (33) on both endothelial and immune cells. Skin biopsy specimens taken from inflamed skin of patients with psoriasis reveal up‐regulation of endothelial cell expression of P‐selectin, E‐selectin, and ICAM‐1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Skin biopsy specimens taken from inflamed skin of patients with psoriasis reveal up-regulation of endothelial cell expression of P-selectin, E-selectin, and ICAM-1 (34). Soluble forms of these molecules are detectable in serum and reflect the severity of the inflammatory reaction in the skin (33). Many studies focused on endothelial cell activity have revealed increased serum levels of soluble E-selectin in psoriatic patients, compared with healthy controls (14,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations